Determinación de enfermedades más comunes en niños de 2 a 12 años de la población aledaña al curso del canal de riego del Consejo Provincial proveniente del Río Jubones sector Nuevo Horizonte de la ciudad de Pasaje. - Estrada Luna, Raquel E. (2005)
Objective: To know the different diseases that children suffer from 2 to 12 years who live in the Sector Nuevo Horizonte of Pasaje the same ones that use the water of the Channel of Watering in different tools, and to determine if the water that you/they consume influences in the appearance of illnesses.